A Capillarity-dependent Model for Prediction of Chloride Penetration Process into Concrete in Artificial Splash Test. Issue 3 (September 2019) - Han, Xun; Guan, Yunfei; Cao, Yongyong; Zhang, Jianyi
Abstract: In order to better simulate the penetration process of chloride ions in the splash zone of concrete, this paper modified existing chloride ion transport model on the basis of capillarity-dependent model under unsaturated and non-pressure conditions to make it applicable to the calcualtion of choride flow flux. The artificial splash tests is firstly designed and conducted under varied conditions of water to cement ratio, splash time duratinoa and splash period. Then the original chloride constitutive model is improved by enhancement of convection term calculation. At last, the authors simulate the chloride ions penetration process under different conditions by reasonble design of equivalent chloride and moisture boundary to verify the effectiveness of capillarity-dependent model.